The Facts on Preharvest Fruit Drop - Vashisth, Tripti (EDIS, 2019)
In citrus, Huanglongbing (HLB) causes an increase in mature fruit drop rate up to 3 months prior to commercial harvest (“preharvest fruit drop”), resulting in a great reduction in yield and difficulty in grove management. In summary, research results demonstrate a clear relationship between HLB severity, fruit size and preharvest fruit drop. Fruit of severely symptomatic trees are smaller and have a higher tendency to drop prior to harvest compared to those of trees displaying less symptoms. This strongly suggests that maintaining tree health is a key to control preharvest fruit drop in HLB-affected trees.